Perbandingan Sintesis Antara Senyawa 2-Metoksikhalkon dan 2,4’-Dimetoksikhalkon dengan Bantuan Iradiasi Gelombang Mikro - Wibawa, Vincentius Tio Putra; Soewandi, Ami; Caroline, Catherine (Jurnal Farmasi Sains dan Terapan, 2018)
Chalcone (1,3-diphenylprop-2-en-1-one) is a precursor compound of flavonoids that have two aromatic rings connected by three α, β-unsaturated carbons. Chalcone can be synthesized by the base-catalysed crossed aldol condensation (Claisen-Schmidt) that reacts aromatic aldehyde with aryl ketone. In this research, synthesize of 2-methoxychalcone and 2,4'-dimethoxychalcone compounds with microwave irradiation assistance had been done. 2-methoxychalcone was synthesized from 2'-methoxyacetophenone and benzaldehyde, while 2,4'-dimethoxychalcone was synthesized from 2'-methoxyacetophenone and 4-methoxybenzaldehyde. The purity of the synthesis compounds were analyzed from melting point and thin layer chromatography data. Identification of structure was performed using infrared spectral data and proton nuclear magnetic resonance. From the obtained results, 2-methoxychalcone and 2,4'-dimethoxychalcone compounds can be synthesized by microwave irradiation assistance. The yield of 2,4'-dimethoxychalcone was 69,69%, while 2-methoxychalcone was 5,15%. The effect of the methoxy group (-OCH3) on benzaldehyde facilitates the reaction formation of khalkon compounds in terms of the yield of synthesis.